The clinical assessment of etodolac and lornoxicam in patients with osteoarthritis (OA) of the knee joint at a tertiary centre in Bihar (Journal of Pharmaceutical Negative Results, 2023)
Background: Osteoarthritis is the most common form of arthritis and one of the leading causes of disability. The present study compared etodolac and lornoxicam in patients of OA of knee joint.Aim and Objectives: The present study was conducted to compare Etodolac and Lornoxicam in patients of OA of knee joint.Materials & Methods: 70 cases of osteoarthritis of knee of both genders were divided into 2 group. Each group comprised of 35 patients. Group I were prescribed tablet etodolac 400 mg twice a day and group II patients were prescribed tablet lornoxicam 8 mg twice a day. Visual Analog Scale (VAS), Western Ontario and McMaster Universities Osteoarthritis index (WOMAC) was reassessed at 3, 6, and 12 weeks after starting treatment. Patient's global assessment at 12 weeks was also recorded.Results: Group I had 20 males and 15 females and group II had 14 males and 21 females. The mean WOMAC was 50.8 in group I and 52.1 in group II at 0 week, 47.2 and 45.8 at 3 weeks in group I and II, 32.6 and 30.1 at 6 weeks in group I and II and 23.3 and 22.1 at 12 weeks in group I and II respectively. The difference was significant (P< 0.05). The mean VAS at 0 wee was 70.6 in group I and 65.4 in group II, at 3 weeks was 48.2 in group I and 38.8 in group II, at 6 weeks was 36.2 in group I and 24.8 in group II and at 12 weeks was 26.0 in group I and 12.1 in group II. The difference was significant (P< 0.05). Adverse effects were pain in 12 in group I and 4 in group II, dyspepsia in 8 in group I and 4 in group II, flatulence in 6 in group I and 3 in group II and nausea in 5 in group I and 2 in group II respectively. The difference was significant (P< 0.05).Conclusion: Etodolac were more efficacious as compared to lornoxicam in patients with knee osteoarthritis.